2018
DOI: 10.1002/ijc.31302
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal factors and pancreatic cancer risk in women: The Malmö Diet and Cancer Study

Abstract: The incidence of pancreatic cancer is leveling between sexes. Smoking, high age and heredity are established risk factors, but evidence regarding the influence of hormonal factors is unclear. In this study, we investigated the associations of reproductive factors, use of oral contraceptives (OC) and hormone replacement therapy (HRT) with pancreatic cancer risk in the Malmö Diet and Cancer Study, a prospective, population‐based cohort encompassing 17,035 women. Up until 31 December 2015, 110 women were identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
36
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 49 publications
(99 reference statements)
0
36
1
1
Order By: Relevance
“… 1 , 2 , 13 Consistent with this, use of estradiol-containing oral contraceptives and history of multiple pregnancies, which correlate with high estrogen exposure, are both associated with decreased PDAC risk. 14 , 15 , 16 Further supporting the idea that PDAC is influenced by estrogen are human clinical trials showing that tamoxifen, which is a GPER agonist, extends survival in PDAC patients. 17 , 18 These data, coupled with a lack of clear evidence that nuclear estrogen receptors are expressed or functional in PDAC, 19 and our RNAseq data ( Supplementary Data ) showing an absence of transcript for both of the classic estrogen receptors (ERα/ERβ) led us to test whether GPER activity inhibits PDAC.…”
mentioning
confidence: 90%
“… 1 , 2 , 13 Consistent with this, use of estradiol-containing oral contraceptives and history of multiple pregnancies, which correlate with high estrogen exposure, are both associated with decreased PDAC risk. 14 , 15 , 16 Further supporting the idea that PDAC is influenced by estrogen are human clinical trials showing that tamoxifen, which is a GPER agonist, extends survival in PDAC patients. 17 , 18 These data, coupled with a lack of clear evidence that nuclear estrogen receptors are expressed or functional in PDAC, 19 and our RNAseq data ( Supplementary Data ) showing an absence of transcript for both of the classic estrogen receptors (ERα/ERβ) led us to test whether GPER activity inhibits PDAC.…”
mentioning
confidence: 90%
“…Whilst the role of female hormone signaling in established pancreatic adenocarcinomas remains unclear, several studies, including research from our group, have suggested an inverse relationship between exogenous and endogenous female sex hormones and risk of pancreatic cancer [1826]. Contrasting findings have however been presented by others [23, 25, 2731].…”
Section: Introductionmentioning
confidence: 84%
“…As with many cancers, women have lower PDAC incidence and more favorable outcomes than men, suggesting that estrogen may suppress PDAC (1,2,13). Consistent with this, use of estradiol containing oral contraceptives, and history of multiple pregnancies, which correlates with high estrogen exposure, are both associated with decreased PDAC risk (14)(15)(16). Further supporting the idea that PDAC is influenced by estrogen are human clinical trials showing that tamoxifen, which is a GPER agonist, extends survival in PDAC patients (17,18).…”
Section: Introductionmentioning
confidence: 87%